Subaltern ecologies in southern Italy - Sciarelli, Roberto (2021)
Italy is a country marked by serious inequalities between its northern and southern regions in terms of welfare, economic production and level of public services. Southern Italy has also suffered serious cases of environmental devastation. A body of literature with a postcolonial approach interprets these inequalities as the outcome of colonial relations of power that have made the south a historic victim of racist representations and authoritarian means of government. Another line of investigation is dedicated to the study of the socio-environmental conflicts which emerged in southern Italy in situations of environmental degradation. The objective of this article is to contribute to build bridges between these two lines of research, identifying the most relevant points of connection and divergence, with the purpose of showing possible paths of common research for a postcolonial political ecology of Southern Italy.